Culture, environment and food to prevent Vitamin A deficiency - Kuhnlein, Harriet V., 1939-; Pelto, Gretel H. (IDRC ; INFDC, 1997)
Aimed at development planners and students of nutrition, public health, anthropology, and human cultural ecology, this book discusses issues surrounding the use of natural sources of food for the prevention of vitamin A deficiency. During a 2-year process guided by the Committee on Nutrition and Anthropology of the International Union of Nutritional Sciences, a protocol was developed to evaluate natural food sources of vitamin A in areas at risk for vitamin A deficiency. This book describes the creation of the ethnographic research tools and their testing in a broad range of cultures and environments in five developing countries. Chapters contributed by research managers in these countries describe the suitability and reliability of the research tools, the data generated, practical applications, and directions for future policy. Many examples are given of helpful new information for planning programs at the local level for alleviating vitamin A deficiency.